Violence and warfare among hunter-gatherers - Allen, Mark W.; Jones, Terry L. (Left Coast Press, 2014)
How did warfare originate? Was it human genetics? Social competition? The rise of complexity? Intensive study of the long-term hunter-gatherer past brings us closer to an answer. The original chapters in this volume examine cultural areas on five continents where there is archaeological, ethnographic, and historical evidence for hunter-gatherer conflict despite high degrees of mobility, small populations, and relatively egalitarian social structures. Their controversial conclusions will elicit interest among anthropologists, archaeologists, and those in conflict studies.